Teaching and researching translation - Hatim, Basil (Pearson Longman, 2012)
This new book introduces students and teachers of translation to the intricacies of the process and demands of the subject. The author shows how theoretical perspectives relate to practical pursuits in translation and interpreting studies and presents relevant research issues and their applications to teaching.